New device for active gastric mechanical stimulation - Prospero, Andre Gonçalves [UNESP]; Pinto, Leonardo Antonio [UNESP]; Matos, Ronaldo Vitor Reis [UNESP]; Soares, Guilherme Augusto [UNESP]; Oliveira, Ricardo Brandt; Mascarenhas, Sérgio; Miranda, José Ricardo de Arruda [UNESP] (Wiley, 2021)
Background: Gastroparesis is a chronic stomach disorder and effective treatment is the aim of different strategies. Alternative therapies consist of an electrical stimulation of the stomach to evoke a response in the gastric activity. We present the development and in vivo application of an electromagnet system to induce a mechanical stimulus in the stomach aiming for gastric contractile responses. Methods: The electromagnet system consisted of an implantable magnet and an external drive coil. We implanted the magnet at the greater curvature of the gastric body in rats. We applied an alternating current to the drive coils, inducing mechanical stimulation of the gastric wall. We measured the gastric contraction activity and gastric electrical activity in response to the stimulus using AC biosusceptometry and electrogastrography. Moreover, we used the phenol red to evaluate the stimulus effects on gastrointestinal transit. Key Results: The stimulus increased the spectral intensity and signal-to-noise ratio significantly of gastric contraction activity and gastric electrical activity. Furthermore, we found a lower phenol red retention in the stomach in rats without stimulus. No significant differences were found in frequency and root mean square amplitude. Conclusions & Inferences: We developed a new simple electromagnet system that evoked a contraction and gastric electrical response using a mechanical stimulus and decreased gastric emptying time. The system is an accessible tool and may contribute to gastroparesis studies in animals.
Keywords: AC biosusceptometry system; electromagnet system; gastric emptying time; gastroparesis; mechanical gastric stimulation